Magnetostratigraphic Age Control of the Timing of Tectonic Deformation and the Shifting Depositional Environments in the Dezful Embayment, Iran. Issue 1 (24th January 2022) - Sun, Jimin; Sheykh, Morteza; Windley, Brian F.; Talebian, Morteza; Cao, Mengmeng; Ahmadi, Nahid; Sha, Jingeng
Abstract: The timing of tectonic deformation in the Zagros foreland basin provides important information about the tectonic propagation process driven by the Arabia‐Eurasia convergence. The chronology of growth strata is one of the most important methods to delimit the history of folding and thrusting within the foreland basin. In this study, we report integrated analyses of sedimentology, magnetostratigraphy, and biostratigraphy of Miocene strata in the Dezful Embayment in the SW Zagros foreland basin. The new results indicate that deposition of the northern limb of the Gach‐e Moh Anticline was between 14.6 and 8.6 Ma; that includes the Upper Gachsaran Formation (14.6–13.8 Ma), the Mishan Formation (13.8–12.8 Ma), and the Agha Jari Formation (12.8–8.6 Ma). Based on magnetostratigraphic and sedimentary evidence, the transition from marine to non‐marine was at ∼12.8 Ma. Analysis of temporal lithofacies‐stacked patterns shows there were seventeen transgression‐regression cycles during the Middle Miocene Climatic Transition with a ∼100‐Kyr Earth eccentricity cycle, suggesting that the cyclic marine transgressions and regressions were mainly driven by eustatic sea level fluctuations; but tectonic‐induced basin subsidence also contributed marine transgressions in the Upper Mishan Formation. The final seawater retreat was at 12.8 Ma driven by both the global eustatic sea level drop and the enhanced south‐westward progradation of sediments eroded from the High Zagros. The base of the growth strata in the footwall of the Mountain Front Fault was at ∼11 Ma, suggesting that tectonic deformation caused by the Arabia‐Eurasia collision had propagated to the Dezful Embayment by that time. Key Points: Magnetostratigraphic chronology in the Dezful Embayment yields an age range of ∼15–9 Ma in the Zagros foreland Tectonic deformation propagated to the Dezful Embayment at 11 Ma driven by the onset of thrusting from the Mountain Front Fault Final seawater retreat in the Dezful Embayment was at 12.8 Ma, and the marine transgressions/regressions had a quasi‐cycle of 100‐Kyr